Association between triglyceride-glucose index and obstructive sleep apnea severity in hypertensive patients with co-existing OSA: a cross-sectional study - Li, Yan; Zhang, Lu; Zhai, Lu; Wang, Limantian; Deng, Shudan; Hao, Xiaolin; Zhang, Ying; Gao, Xiaoling (Frontiers in Endocrinology, 2025)
Study objectivesTo evaluate the association between the triglyceride-glucose (TyG) index and obstructive sleep apnea (OSA) severity in hypertensive patients with comorbid OSA, particularly in non-obese subgroups.MethodsThis cross-sectional study consecutively enrolled 653 hypertensive patients with snoring and excessive daytime sleepiness from the Second Hospital of Shanxi Medical University between 2022 and 2023. After confirming OSA diagnosis by polysomnography, 562 eligible participants were stratified into mild/moderate/severe OSA groups. The TyG index was calculated as ln[fasting triglycerides (mg/dL) × glucose (mg/dL)/2]. Multivariable ordinal logistic regression was performed to identify predictors of OSA severity, with subgroup analyses stratified by BMI. Linear regression was employed to examine the association between the TyG index and the apnea-hypopnea index (AHI).ResultsIn the fully adjusted model, the TyG index showed the strongest independent association with OSA severity progression (OR = 1.885, 95%CI:1.107-3.209), demonstrating greater explanatory value than BMI based on standardized β coefficients. This association demonstrated striking phenotypic specificity, with significant correlation restricted to non-obese individuals (adjusted OR = 2.804, 95%CI:1.547-5.083) versus obese counterparts. Stratification by TyG tertiles revealed progressive AHI escalation with increasing tertiles (β = 8.265 per tertile, P < 0.001), indicating a dose-response relationship.ConclusionsThe TyG index surpasses conventional obesity metrics in stratifying OSA severity among hypertensive patients with OSA. These findings support its utility as a pathophysiology-guided risk stratification tool for OSA-related cardiometabolic complications in hypertension management.